2013
DOI: 10.2527/jas.2013-6328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insoluble-low fermentable fiber from corn-ethanol distillation origin on energy, fiber, and amino acid digestibility, hindgut degradability of fiber, and growth performance of pigs1

Abstract: Extensive use of corn coproducts in swine diets increases the concentration of dietary fiber, raising concerns on energy and nutrient digestibility and, ultimately, pig performance. A digestion trial was conducted to determine the effect of increasing levels of insoluble-low fermentable fiber from corn in the diet, using corn bran with solubles (CBS) from the corn-ethanol distillation industry, on digestibility of energy, fiber, and AA, and hindgut fermentation of fiber in diets fed to growing pigs. Fifteen gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 45 publications
(54 reference statements)
11
45
2
Order By: Relevance
“…In the current experiments, feeding DDGS affected performance only in the young pig and generally decreased ATTD of energy and many of the nutrients measured. Our data are supported with previously published data sets on the impact of feeding DDGS on ATTD of energy and nutrients and growth performance in pigs, which has been discussed extensively elsewhere (Stein and Shurson, 2009;Cromwell et al, 2011;Gutierrez et al, 2013Gutierrez et al, , 2014aKerr et al, , 2015aWu et al 2016a,b,c), and was not one of the main objectives of the current experiment.…”
Section: Discussionsupporting
confidence: 92%
“…In the current experiments, feeding DDGS affected performance only in the young pig and generally decreased ATTD of energy and many of the nutrients measured. Our data are supported with previously published data sets on the impact of feeding DDGS on ATTD of energy and nutrients and growth performance in pigs, which has been discussed extensively elsewhere (Stein and Shurson, 2009;Cromwell et al, 2011;Gutierrez et al, 2013Gutierrez et al, , 2014aKerr et al, , 2015aWu et al 2016a,b,c), and was not one of the main objectives of the current experiment.…”
Section: Discussionsupporting
confidence: 92%
“…Dietary fats (Cervantes-Pahm and Stein, 2008;Kil and Stein, 2011) and fibers (Gutierrez et al, 2013) have been reported to influence AA digestibility values. In the present work, however, we failed to find significant correlations between ether extract or fibers and AA digestibility values (data not shown) likely due to the quite constant concentrations of ether extract and fibers in the corn sources.…”
Section: Discussionmentioning
confidence: 98%
“…It has been hypothesized that dietary fiber does not have a significant effect on growth performance, which implies that pigs can tolerate a wide range of dietary fiber levels, if dietary energy density is adequate (Baird et al, 1975;Beaulieu et al, 2009;Gutierrez et al, 2013). In our study, the slight decrease in carcass yield might have occurred because of an increase in intestinal content and/or increased organ development, although the effect was negigible after the usual pre-slaughter fasting periods (12-24 h) used (Santomá, 1997).…”
Section: Effect Of Increasing Dietary Andfommentioning
confidence: 99%